2018
DOI: 10.1186/s12889-018-6281-0
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to customize responsible gambling messages: a review and focus group study

Abstract: BackgroundResponsible gambling messages are widely used as a tool to enable informed choice and encourage appropriate gambling behavior. It is generally accepted that gamblers have different levels of risk of developing gambling problems and require various harm minimization tools and resources. Therefore, it is reasonable to expect that responsible gambling messages should be customized and target specific groups of gamblers. This project aimed to understand hypothesized differences between cohorts of gambler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 97 publications
0
29
0
Order By: Relevance
“…Allaying any concerns that the efforts to encourage CPT use in this study or by gambling sites in the future may lead to high rates of irritation or site abandoning, research has found customers are not inconvenienced by the promotion of CPTs, including those at different risk levels for gambling problems (3). Future research in live gambling environments is required to determine the effectiveness of targeted messages sent in response to certain risk behaviours (14), as well as messages tailored to individuals and based on cohort preferences, both of which have shown preliminary value as customisation strategies (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Allaying any concerns that the efforts to encourage CPT use in this study or by gambling sites in the future may lead to high rates of irritation or site abandoning, research has found customers are not inconvenienced by the promotion of CPTs, including those at different risk levels for gambling problems (3). Future research in live gambling environments is required to determine the effectiveness of targeted messages sent in response to certain risk behaviours (14), as well as messages tailored to individuals and based on cohort preferences, both of which have shown preliminary value as customisation strategies (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Although we examined tool use based on several self-reported participant characteristics, future research should identify relevant customer segments, including those who would most benefit from using specific tools. This is important to enable targeted marketing strategies, that is, sending specific, customised messages to segments to increase the perceived relevance of these and impact on behaviour (Auer & Griffiths, 2016;Gainsbury, Abarbanel, Philander, & Butler, 2018).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Skills are important in poker gambling and poker gamblers have been demonstrated to have particular thoughts about their own gambling behavior and to be particularly sensitive to feedbacks on their own practice [11]. Illusion of control could be high in poker gamblers [12] and perception of their own skills could be amplified [13].…”
Section: Introductionmentioning
confidence: 99%